HIV and other sexually transmitted infections among men, transgenders and women selling sex in two cities in Pakistan: a cross-sectional prevalence survey. (23rd March 2009) - Hawkes, S; Collumbien, M; Platt, L; Lalji, N; Rizvi, N; Andreasen, A; Chow, J; Muzaffar, R; ur-Rehman, H; Siddiqui, N; Hasan, S; Bokhari, A
Abstract : Objectives: The extent and possibilities of spread of the HIV epidemic are not fully understood in Pakistan. A survey was conducted among men, women and transgender populations selling sex in Rawalpindi (Punjab) and Abbottabad (North West Frontier Province) in order to inform evidence-based programme planning. Methods: A cross-sectional survey was performed with participants recruited through respondent-driven sampling. Male and transgender sex workers were analysed in three gender groups; women were analysed as one group. Behavioural surveys were conducted and clinical specimens collected. Laboratory tests looked for evidence of acute infection (gonorrhoea, Chlamydia, syphilis, Trichomonas ) and infection over the lifetime (HIV, herpes simplex virus-2, syphilis). Predictors of infection were explored using univariable and multivariable logistic regression. Results: The prevalence of HIV was low in 917 male and transgender sex workers and absent in 533 female sex workers in the study. High levels of current sexually transmitted infections were found, predominantly among transgender sex workers. Risk behaviours were common and knowledge of HIV was extremely low. Multivariable analysis found a large number of factors associated with higher levels of infection, including experience of forced first sex. Protection against risk was low, but those sex workers who reported using condoms at last sex had lower rates of infection. Conclusions: The HIV epidemic is currently in its early stages among people who sell sex, but there may be potential for a much greater spread given the levels of other sexually transmitted infections found and the concomitant low levels of both protective knowledge and risk-reducing behaviours. Action is needed now to avert an epidemic. Framing interventions by upholding the recognition and protection of human rights is vital.